The effects of maternal dietary salt intake during pregnancy and lactation on the offspring blood pressure in rats - Aminuddin , Niferiti; Mohd Noor, Noriah; Mohd Rashid, Muhammad Hakimi; Tin , Myo Han; Azzubaidi, Marwan Saad; Abdul Razak, Tariq (2014)
Perinatal programming is a concept introduced by Barker and colleague (1992).It refers to development of chronic diseases such as hypertension and cardiovascular diseases in adulthood as a result of abnormal environment or an insult during a critical period of fetal development during pregnancy and lactation.  One model of perinatal programming includes the effects of different maternal dietary sodium concentration during pregnancy and lactation on the offspring’s blood pressure (Koleganova et al., 2011). This study aims at investigating the effects of high (3.0%NaCl) and low (0.145%NaCl) maternal dietary sodium concentration on their offspring’s blood pressure at 4 and 8 weeks in comparison to normal maternal dietary sodium concentration (1.0% NaCl). ). Normotensive female Sprague-Dawley rats were subjected to timed- pregnancy. . Pregnant rats were randomly divided into three groups and were fed either low-sodium diet (LSD) (0.145%NaCl) (n=10), normal-sodium diet (NSD) ( 1.0%NaCl) (n=10) or high-sodium diet (HSD) (3.0%NaCl)(n=10) during pregnancy and 4 weeks of lactation. The offsprings were weaned at 4 weeks old. Thereafter, all the three groups were fed with normal-sodium diet (1.0%NaCl) for another 4 weeks. At 4 weeks old, the offsprings of HSD dams have significantly higher systolic blood pressure (SBP) compared to NSD group respectively (119.44mmHg ±1.8 vs 103.65mmHg ±0.92). There were no differences in the offspring’s SBP between NSD and LSD dams at 4 weeks old. Nevertheless, at 8 weeks old, the offspring’s of LSD dams have significantly higher SBP as compared to NSD dams (130.13±1.45mmHg vs 120.26mmHg±1.09). Similarly, at 8 weeks old, the offspring of HSD dams have significantly higher SBP as compared to NSD dams (131.06±1.49mmHg vs 120.26mmHg±1.09). However the SBP is still within normal range and LSD manifest higher SBP at later age as compared to HSD offspring. There were similar mean daily food intake between week 4-8 (g/day)(17.02±0.14;16.76±0.12;17.14±0.12) and mean body weight at 4 (92.12±0.44g; 92.69±0.57g; 93.01±0.73g) and 8weeks (299.39±1.51g;297.97±1.25g; 301.95±1.63g)  in the offspring  of LSD,NSD and HSD   dams respectively. If these findings can be extrapolated in human, both too low and too high salt intake during pregnancy would be a risk factor for hypertension in the offspring.  This suggests that there is an optimal level of dietary sodium intake during gestation and lactation.